ТЕРАПЕВТИЧНІ МІШЕНІ МОЛЕКУЛЯРНИХ СИГНАЛЬНИХ ШЛЯХІВ У КЛІТИНАХ КОЛОРЕКТАЛЬНОГО РАКУ - Ebru Nur, A. (PH Akademperiodyka, 2023)
Mutations in tumor suppressor genes, cell signaling, and genes associated with DNA repair lead to onset of colorectal cancer (CRC). Even though most CRC patients get clinical benefits from conventional treatments such as chemotherapy and radiotherapy, treatment success is still not at the desired level despite recent advances in CRC treatments. Therefore, further elucidation of the molecular signaling pathways involved in CRC progression will allow developing targeted therapies. With the detection of signaling pathways that lead to cancer progression and development of the successful treatment methods targeting these pathways, the progression of the disease can be prevented. This review provides an overview of the therapeutic roles of potential molecular targets in recent preclinical and clinical studies in CRC treatment.